2019
DOI: 10.1021/acs.analchem.9b03824
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Colorimetric Detection of a Variety of Analytes via the Tyndall Effect

Abstract: This work initially reports the use of a quite familiar optical phenomenon of colloidal solutions, namely, the Tyndall Effect (TE) as signal readout for highly sensitive colorimetric chemical and biological analysis. Taking gold nanoparticles (GNPs) as a model colloid, the TE-inspired assay (TEA) is developed based on the conversion of a specific recognition event (e.g., the aptamer–analyte binding) into the aggregation of GNPs, leading to a significant TE enhancement. In the TEA, a cheap laser pointer pen is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…Tyndall effect was observed in the solution of [CuCl(pip) 2 ]Cl in proton solvent CH 3 CH 2 OH/H 2 O (Figure 6), indicating the formation of self-assembled species [46], while no Tyndall phenomenon observed in aprotic solvent DMF. Therefore, the presence of proton solvent could be a determining factor for the self-assembly, as proton solvent could provide H atom feasible for the aggregation driven by hydrogen bond.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Tyndall effect was observed in the solution of [CuCl(pip) 2 ]Cl in proton solvent CH 3 CH 2 OH/H 2 O (Figure 6), indicating the formation of self-assembled species [46], while no Tyndall phenomenon observed in aprotic solvent DMF. Therefore, the presence of proton solvent could be a determining factor for the self-assembly, as proton solvent could provide H atom feasible for the aggregation driven by hydrogen bond.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Overall, the presented operando TE-based approach constitutes a signi cant progress in analytical strategies aiming at investigating the dynamics of the interfacial double layer because it provides instantaneous extended pH read-out on surfaces with distinct local reactivities and unique spatiotemporal resolution only limited by the acquisition capabilities of the employed camera (here 30 three-dimensional reactivity maps per second). Besides straightforwardly enabling comparative reaction kinetics intrinsic to complex electrode architectures, the approach is also amenable to quanti cation and exhibits outstanding sensitivity 28 . Finally, its applicability can be universally extended to any other nanoaggregation/decomplexation process of interest (e.g., electrocoagulation, mineral removal and separation, electrosynthesis, among others) occurring at light-addressable interfaces provided the probed colloids are smaller than the wavelength of visible light.…”
Section: Con Rmation By Numerical Simulationsmentioning
confidence: 99%
“…This phenomenon has already been used as a visual screening method to detect microprecipitates in blends of parental drug solutions 22,23 as well as to evaluate nanolevel aggregation and characterise colloidal catalyst and functional materials [24][25][26][27] . More recently, Xiao et al 28 added quantitative character to a TE-based colorimetry approach and demonstrated a ca. 1000-fold sensitivity improvement compared to common surface plasmon resonance-based techniques.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, another powerful optical property of the colloidal metal nanoparticles like the AuNPs-Tyndall effect (TE)-has been explored for enhanced colorimetric signaling. [25][26][27] The TE, which is named for the 19th-century British physicist John Tyndall, is dened as the bright "pathway" formed when a light beam passes a colloidal solution due to the scattering effect of the colloidal particles on the light. 28,29 Its intensity positively relies on both of the particle size and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…However, the previous AuNP-based TEAs still suffer from the disadvantages of multi-step nanoprobe modication, relatively tedious analytical time ($1 h), and/or more ideal assay specicity remains a big challenge. 25,26 With these insights, herein we initially describe the proof-ofconcept of a new TEA method that combines the unmodied (bare) AuNPs with functional nucleic acids for the rapid, highly specic visual detection and quantication of Hg 2+ ions at nM levels. Considerable studies have proven that the thymine-rich single-stranded DNA (ssDNA) possesses an excellent selective binding affinity to Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%